2015
DOI: 10.1590/1807-1929/agriambi.v19n8p748-754
|View full text |Cite
|
Sign up to set email alerts
|

Yield of cotton cultivars under different irrigation depths in the Brazilian semi-arid region

Abstract: A B S T R A C TThe objective of this study was to evaluate the effect of irrigation depths on seed cotton yield and water-use efficiency of cotton cultivars in the Brazilian semi-arid region. Field experiment was conducted during two consecutive years in the Apodi region, RN, using sprinkler irrigation. The experiment consisted of factorial combination in split-plots, composed of four irrigation depths (130; 100; 70 and 40% ETc and four cotton cultivars -FiberMax 993, BRS 286, BRS 336 and BRS 335), in randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
3
12
1
3
Order By: Relevance
“…The results of the present study corroborate those of [23], who observed increase in cotton yield as water replacement increased, and are also consistent with those found by [7], who observed quadratic fit of cotton yield with higher K supply in the soil and in the leaf. When the crop received only the irrigation necessary to replace 100% ETC using treated domestic wastewater, SCW was equal to 29.0 g plant -1 , similar to the value obtained in the absolute control.…”
Section: Seed Cotton Weightsupporting
confidence: 93%
“…The results of the present study corroborate those of [23], who observed increase in cotton yield as water replacement increased, and are also consistent with those found by [7], who observed quadratic fit of cotton yield with higher K supply in the soil and in the leaf. When the crop received only the irrigation necessary to replace 100% ETC using treated domestic wastewater, SCW was equal to 29.0 g plant -1 , similar to the value obtained in the absolute control.…”
Section: Seed Cotton Weightsupporting
confidence: 93%
“…Other research studies corroborate all the evaluated variables, such as Zonta et al (2015b), who have studied the effect of irrigation on yield and fiber quality in upland cotton cultivars; Zonta et al (2017), who have studied the influence of sampling on the analysis of the fiber quality of irrigated and water stressed cotton; and Almeida et al (2016), who have studied the effect of periods of water deficit in different phenological stages for cotton fiber quality, who have also found significant differences between treatments and cultivars studied for fiber variables at 1% probability level.…”
Section: Resultssupporting
confidence: 71%
“…According to Bradow and Davidonis (2000), fiber color is directly linked to environmental factors during the growing season, which in this work was the water stress in different phenological stages. Zonta et al (2015b) state that factors such as the application of defoliants and desiccants, pest attack, among others, can also influence fiber color.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted, showing that prolonged water deficit during the cotton cultivation cycle affects growth, productivity, and quality of the fibers (SNOWDEN et al, 2013;ZONTA et al, 2015a, ZONTA et al, 2015b.…”
Section: Introductionmentioning
confidence: 99%